Pengembangan Kompetensi Pegawai Negeri Sipil (PNS) Di Daerah: Tantangan dan Peluang - Rati Sumanti (Jurnal Transformasi Administrasi, 2018)
To perform the task, every civil servant must have adequate competence in managerial, socio-cultural and technical competence. Government agencies both central and regional are required to develop civil servant’s competencies that aim to develop the quality of knowledge, skills and behavior of civil servants so that they can perform the task well. This research aims to understand the development competence of civil servants in the local government. The result of research using qualitative approach with secondary data collection technique through literature study, obtained some challenges and opportunities faced by local government institution in doing civil servant development. The law about Aparatur Sipil Negara requires government agencies to fulfill the right of civil servants to get competence development from a minimum of twenty hours per year. To implement it, there are some challenges faced namely the gap between the competency standard of an office and the competence of the employee. In addition, there is no document of competency development plan in each agency and limited budget allocation in the local government to finance the planned competency development activities. As an effort to overcome these challenges, it needs creativity and innovation as an opportunity from government institution to fulfill the right of civil servant’s competency development.